Personalizing Decision-Making for Patients Choosing Contralateral Prophylactic Mastectomy: A Utility Analysis of Genetic Factors and the Relative Risk of Breast Cancer. Issue 4 (November 2019) - Campwala, Insiyah; Yoo, June; Gupta, Subhas
Introduction: There has been an increasing trend of patients with breast cancer electing to undergo contralateral prophylactic mastectomy (CPM), despite the lack of evidence showing long-term survival benefit. We aim to quantify the tiered amount of genetic and surgical complication risk deemed necessary to justify CPM. Methods: A review of breast cancer–affiliated genetic mutations and morbidity rates of breast cancer surgery from a single institution was compiled. A survey using a utility analysis was created. Severity of breast cancer genetic risk and morbidity risk warranting CPM was quantified and evaluated. Results: A total of 143 surveys were submitted by women of the general population. Data analysis confirmed previous predictions that at a hypothetical increased risk of contralateral breast cancer (CBC), about twice the proportion of women will elect CPM. With over 10 times the baseline risk and no surgical complications, 98.6% of women chose CPM. There was a decrease in affirmative responses with increasing morbidity. This decrease was least prominent at higher genetic risk, illustrating that when women are at a higher risk of CBC, the surgical morbidity rate has less of an impact on their decision for CPM. Conclusion: At increased risk of CBC, women are likely to elect for CPM. We anticipate that these findings will encourage the growing use of personalized medicine, with the potential to tailor breast cancer treatment plans for each patient's personal genetic profile.